CLONAGEM E EXPRESSÃO DO GENE DA GLICOPROTEÍNA S1 DO VÍRUS DA BRONQUITE INFECCIOSA DAS GALINHAS EM PICHIA PASTORIS - Gonçalves, M.c.m [UNESP] (2021)
Genetic and antigenic variation are very frequently observed among IBV strains and affect mainly the S1 glycoprotein. In order to contribute to the availability of tools for immunodiagnosis and immunoprophylaxis of chicken infectious bronchitis we developed an expression system for production of recombinant S1 glycoprotein in Pichia pastoris. We obtained the cDNA from viral RNA on embryonated eggs infected with the M41 strain of IBV, by reverse transcription (RT) and polymerase chain reaction (PCR), amplifying the S1 coding sequence with extremities compatible with the vector used to transform yeast. Induction with methanol led to the production of a protein with the predicted molecular weight that was detected by Western blot in the cell lysate of transformed yeast. Expression in P. pastoris proved to be an effective method for recombinant production of S1 protein from IBV, with potential for use in immuno-diagnosis of chicken infectious bronchitis virus.